2007
DOI: 10.1016/j.urology.2007.06.1093
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Screening in Men with a Family History of Prostate Cancer: The Role of Partners in Influencing Men’s Screening Uptake

Abstract: Psychological factors are the most important influence on men's uptake of DRE, whereas external factors, including partner's involvement, influence PSA uptake. If prostate cancer screening is ultimately shown to be efficacious for men with a family history of prostate cancer, screening uptake will be maximized in this target group by enlisting the support of partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 25 publications
(47 reference statements)
3
30
1
1
Order By: Relevance
“…We have previously reported that the greatest need of men with a family history of prostate cancer was to obtain information about risk management 25 and that most are managing their risk by undergoing surveillance. 26 In this study, we extend these data by considering other modifications men have made to their health behavior, finding that 39% reported having made changes in response to their family history alone. For instance, the belief that diet could affect risk was widely held (73%) and many (27%) had already modified their diet on the basis of their family history.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…We have previously reported that the greatest need of men with a family history of prostate cancer was to obtain information about risk management 25 and that most are managing their risk by undergoing surveillance. 26 In this study, we extend these data by considering other modifications men have made to their health behavior, finding that 39% reported having made changes in response to their family history alone. For instance, the belief that diet could affect risk was widely held (73%) and many (27%) had already modified their diet on the basis of their family history.…”
Section: Discussionmentioning
confidence: 51%
“…26 The study was approved by the ethics committees of Melbourne Health and The Cancer Council Victoria. Questionnaires and reply paid envelopes were mailed through each of the primary study centers.…”
Section: Methodsmentioning
confidence: 99%
“…Other research has reported that men whose partners were highly involved in men's screening decisions had a significantly higher uptake of prostate-specific antigen (PSA) testing compared with single men and men whose partners had low involvement (Meiser et al, 2007). Moreover, although quantitative evidence suggests that being married improves the likelihood that a man will be screened for prostate cancer (McFall & Davila, 2008;Merrill, 2001;Ross et al, 2004;Seo & Lee, 2010), significant questions remain regarding these family dynamics.…”
mentioning
confidence: 99%
“…To assign a lower contribution value to the opposite-sex intervention would have been to relegate a potential service for someone with whom an emotional attachment existed. Unsurprisingly, cohabiting is a strong predictor of actual participation in cancer screening, sex-specific or otherwise (Meiser et al, 2007;van Jaarsveld et al, 2006;von Euler-Chelpin et al, 2008). Presumably, the desire to alleviate one's own concerns about one's susceptibility to illness is reinforced by the need to alleviate the same concerns of one's partner.…”
Section: Discussionmentioning
confidence: 99%